STRATEGI PENGENALAN POTENSI ANAK - Makmun Zahruddin (Tamaddun, 2018)
Basically, humans have two great abilities, namely the actual ability and potential ability. Actual abilities are abilities that exist today, abilities that have already been seen. This can be seen (in part) for example from IQ scores, TOEFL scores, and academic scores. Potential abilities are abilities that have not yet been seen, abilities that have the opportunity to develop; Therefore to develop it requires stimulants from the environment (education, parents, teachers, nutrition), for example talents. This article tries to identify several potentials and how to identify them. To identify the potential is needed for teachers to understand their children by understanding the child's growth and developmental tasks at each stage. Ways to identify the potential of children can use two things, namely by identifying the child's talents and knowing their interests (child's personality). Children's talent can be identified from general abilities (intelligence), creativity, and motivation.